Sovereignty across generations : constituent power and political liberalism - Ferrara, Alessandro, 1953- (Oxford : Oxford University Press, 2023)
Every cohort of voters may dream of being 'the people' under the sway of serial visions of sovereignty; or understand itself, more modestly, as co-author of a constitutional project in a cross-generational sequence rooted in the past and extending into the future. This book offers a theory of democratic sovereignty and constituent power grounded in John Rawls's political liberalism.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 24, 2023).
Keywords: Sovereignty; Constituent power; Liberalism; Politics and Government; Politics & government